Early one-stage posterior-only surgery for congenital cervicothoracic scoliosis in children: medium- and long-term follow-up - Zhang, Cefei; Liu, Fuyun; Xu, Ke; Hu, Weiming; Xia, Bing; Zhao, Yufeng (Frontiers in Surgery, 2025)
ObjectiveThe purpose of this study is to investigate the medium- and long-term correction outcomes and complications of early one-stage posterior-only surgery for congenital cervicothoracic scoliosis in children.MethodsFrom March 2006 to March 2022, we retrospectively investigated 33 consecutive cases of congenital cervicothoracic scoliosis treated by one-stage posterior-only surgery, including 15 males and 18 females, with a mean age of 3.2 years. Radiographic parameters, including segmental scoliosis, distal compensatory curve, T1 tilt, clavicle angle, neck tilt, coronal balance distance, segmental kyphosis, and sagittal vertical axis, were measured preoperatively, postoperatively, and at the last follow-up. The results of the measurements were statistically analyzed using paired-sample t-tests. Complications were recorded.ResultsThe mean operation time was 199.8 min (100–340 min) with an average blood loss of 261.5 ml (80–600 ml). The mean follow-up period was 75.8 months (28–182 months). Fusion levels averaged 3.4 segments (2–6 segments). The segmental scoliosis was improved from 48.2° ± 10.7° preoperatively to 10.0° ± 6.0° postoperatively (P < 0.001), with a correction rate of 79.3% ± 11.2%. The distal compensatory curve was spontaneously corrected from 23.4° ± 9.8° preoperatively to 9.2° ± 5.7° postoperatively (P < 0.001), with a correction rate of 58.8% ± 19.4%. One case of pleural rupture, three cases of transient nerve root injury, one case of Horner syndrome, and two cases of pleural effusion. Two cases underwent revision surgery due to loss of correction.ConclusionEarly one-stage posterior-only surgery for congenital cervicothoracic scoliosis in children can effectively correct the local deformities and improve the appearance, and the medium- and long-term correction outcomes are satisfactory. Hemivertebra resection without internal fixation may be considered for some very young children. For the higher level of thoracic hemivertebra, the osteotomy level being shifted down one vertebra is a feasible and safer surgical procedure.